A microbiologia no âmbito das ciências ambientais: segundo o livro didático e os documentos norteadores do componente curricular biologia do ensino médio no estado do Paraná - Sartori, Maristela Aparecida (2023)
When talking about education and training for teenagers and young people, we thought about what kind of people we want to train. According to the BNCC, this construction must be based on integral human development, which encompasses all aspects: intellectual, physical, emotional, social and cultural, in the sense that students are able to build a more supportive, inclusive, ethical, responsible society, fair and sustainable. Thus, the student manages to establish a relationship between the formal contents seen at school and the applicability of this knowledge in their experimental experiences. The microbiology, which address microscopic living beings or microorganisms, are part of our environment, and of our daily life, whether in health, the environment, the application of biotechnologies, among others. These microorganisms can be negative or harmless and even necessary in many cases. These are viruses, bacteria, protozoa, algae and fungi. To focus on the great importance of this content, since microorganisms were the first inhabitants of the planet and are used on a large scale in various sectors, such as in the food and pharmaceutical industries, in bioremediation as depolluting agents, there is a need for their study and understanding by the high school student, in understanding this importance, appropriating this knowledge in a transforming way, building a new meaning in their life. These contents to be seen must be in line with the textbooks used in the classroom and the documents that guide the educational system at the federal, state and municipal levels.